Do Entrepreneurial Marketing and Internet Marketing Impact On Business Performance? (Case Study Ornamental Plant Agribusiness in Banyumas) - Fajri, Wahid Nur; Any Suryantini; Masyhuri (Jurnal Manajemen & Agribisnis, 2023)
The marketing system continues to develop along with the development of digital technology. Moreover, since 2020, the Covid-19 pandemic has occurred, which requires consumers to buy goods without meeting directly with the seller using digital-based commercial media. In Banyumas, purchasing agricultural products such as ornamental plants also use digital media. This study aims to determine the characteristics of ornamental plant business actors in Banyumas, analyze the achievements of entrepreneurial marketing, internet marketing, and business performance of ornamental plant businesses in Banyumas, analyze the direct and indirect effects of entrepreneurial and internet marketing on business performance of ornamental plant businesses in Banyumas. The data used are primary data using a questionnaire, and as many as 150 respondents were determined by quota sampling. The analysis results obtained that most of the ornamental plant business actors in Banyumas are men, aged 39-48 years, have an elementary school education, use rental land, and are spread across Baturraden, Sumbang, Kedungbanteng, Karanglewas Districts. The achievements on the latent variables of entrepreneurial marketing, internet marketing, and business performance are quite high, namely in the 60-80% range. Based on SEM analysis with the PLS approach (SEM-PLS), it is known that the latent variables of entrepreneurial marketing and internet marketing positively affect business performance. However, training is needed to improve internet marketing skills for ornamental plant business actors in Banyumas. Keywords: entrepreneurial, internet, business performance, ornamental plant, SEM PLS